PENGARUH PENDEKATAN KUALITATIF DALAM RISET PEMASARAN DAN PENGUKURAN PADA KINERJA BISNIS - Baiza, Ahmad; Uran, Alfonsus Vianey Nara; Fadhilah, Muinah (Transpublika Publisher, 2022)
This study aims to discuss qualitative approaches in marketing research as part of measuring business performance today. This research examines the similarities and differences between three qualitative research methods: phenomenology, grounded theory, and ethnography. Research will be beneficial to the development of theories and will assist in the making of sound business decisions. This study demonstrates that qualitative research methods are now considered appropriate for use in consumer research as well as marketing in general. This article presents a research method that takes a qualitative approach and discusses some of the potential applications of that method in marketing research and the measurement of business success.